Contour Cutting with Scissors – A Study on Manual Dexterity and Time Management - Elena-Simona Indreica (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2024)
The article presents a study on the relationship between manual dexterity and time management, considering contour cutting with scissors as an indicator of manual dexterity. A sample of students completed a questionnaire measuring time management skills and performed several tasks designed to evaluate manual dexterity. After data analysis, we obtained a significant positive correlation between manual dexterity and time management. This result may be an argument for an individualized occupational therapy program. There were also significant differences between correct contour cutting with scissors and non-correct contour cutting with scissors in terms of manual dexterity and time management. Starting from the obtained results, we conclude that the contour cutting technique with scissors can be a practical solution for developing manual dexterity and optimizing time management